SOME QUESTIONS OF THE THEORY OF DRY FRICTION - Jurov, V. M.; Ibraуev N. H.; Guchenko, S. A.; Huanbai, E. (Recent Contributions to Physics, 2011)
Expression for factor of friction and the superficial tension, taking into account geometry of a surface and its physical properties is received. The conclusion that it is impossible to use homogeneous pairs metals in antifrictional pairs friction is made. It is shown, that reduction of factor of dry friction is possible due to reduction of superficial energy at use of pairs friction at which work of an output considerably differs.